(untitled) (Revista Internacional de Folkcomunicação, 2019)
In Vitória da Conquista, groups of Terno de Reis from ancient tropeiros and religious choirs perform in the Natal da Cidade project. Understood as a flow of massive communication, the event diffuses and feeds back a system of memory and identitary conflicts within the calendar of religious tradition anchored at the heart of local festivities. This article presents results of research that analyzed the conjunctures and intermediations of Ternos de Reis, Tropeirismo, and choirs in their relations of sociability and representativeness within the media chain of the party. An interdisciplinary methodology was adopted that prioritized the ethnographic fieldwork. At the end of the whole process, it was concluded that there is an unequal force relation between the presented attractions, whose inequality is evidenced as coming from the historical process, amplified by the model of spectacularization and social representation. Folkcommunication; Memory; Natal da Cidade Project; Terno de Reis; Tropeirismo.